Water Pollution - VERMA, PUSHPLATA (SCHOOL SCIENCE, 2006)
Pollution is one of the major environmental problems these days. The term pollution has been defined in a variety of ways. According to E.P. Odum, pollution is an undesirable change in the physical,chemical or biological characteristics of our air, land and water that will harmfully affect the human life and the desirable species, or that may waste or deteriorate our raw material resources. In Environmental (protection) Act, 1986 of India “environmental pollutant” means any solid, liquid or gaseous substance present in such concentration as may be or tend to be injurious to environment; and ‘environmental pollution” means the presence in the environment of any environmental pollutant. There are two basic types of pollutants.